Pericardial Effusionin Patients Admitted in Emergency Department: Frequency and Causes - Bakht Umar Khan, Fayaz Ahmed Memon, Muhammad Shehram, Muhammad Shahid, Fahad Khalid, Nayyar Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:A study of pericardial effusions in individuals with dyspnea was conducted to evaluate the prevalence and aetiology. Study Design:Prospective/Observational Study Place and Duration: Multicenteric study conducted at DHQ Hospital Bagh AJK/ Federal Govt. Polyclinic Hospital Islamabad and DHQ Teaching Hospital Gujranwala Medical College, Gujranwala. Duration was six months from 1st Oct 2021 to 31st March 2022. Methods:There were 135 patients of both genders had ages 18-75 years were presented in this study. Patients with dyspnea were admitted to emergency department. After obtaining informed written consent, we compiled detailed demographic information on all enrolled patients.Pericardial effusion was detected in all cases using echocardiography.The causes of pericardial effusion have been studied." SPSS 22.0 was used to analyze the data. Results: There were 75 (55.6%) males and 60 (44.4%) females in this study. Mean age of the patients was 58.16±10.79 years and had mean BMI 23.9±10.45 kg/m2. Majority of the patients were illiterate 90 (66.7%) and 45 (33.3%) were literate. We found frequency of pericardial effusions among 26 (19.3%) cases. Majority were males 17 (65.4%) and 9 (34.6%) were females. Most common cause of pericardial effusions were neoplastic diseases 10 (38.5%), idiopathic found in 8 (30.8%) cases, 3 (11.4%) had uremia, bacterial infections in 2 (7.7%) cases, frequency of HIV cases was 2 (7.7%) and 1 (3.8%) had other causes. Among 26 patients of pericardial effusions, small size effusion found in 14 (53.8%) cases, moderate size in 8 (30.8%) cases and large size in 4 (15.4%) cases. Conclusion: According to this study,patients with unexplained dyspnea had an increased risk of developing pericardial effusion,. The most prevalent cause of pericardial effusion was a neoplastic disease.